2017
DOI: 10.1177/0022466917719260
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Literacy With Self-Created Grocery Lists on Mobile Devices

Abstract: Four middle school students with a developmental disability participated in a multiple probe design across students and replicated across conditions study to evaluate the effectiveness of constant time delay to teach them to create a grocery list on an iPad or iPod touch. The classroom teacher collected data on the percentage of items independently added to their electronic list and generalization measures to longer lists with novel items and using a different device. In addition, she administered a pre- and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…None of the studies reported a systematic assessment of the digital skills of participants before starting the intervention. However, 14 studies reported participants’ previous experience with a digital device (Ayres & Cihak, 2010; Bereznak et al, 2012; Burckley et al., 2015; Cannella‐Malone et al, 2006; De Wit et al., 2015; Douglas, Uphold, Steffen, & Kroesch, 2018; Mechling et al., 2009; Mechling & O’Brien, 2010; Shepley, Spriggs, Samudre, & Elliot, 2018; Smith et al., 2016; Smith, Shepley, Alexander, Davis, & Ayres, 2015; Spriggs et al., 2015; Van Laarhoven, Blood, Chan, & Winiarski, 2012; Van Laarhoven, Kraus, Karpman, Nizzi, & Valentino, 2010). These experiences varied from playing online games to executing simple acts on a computer such as typing letters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…None of the studies reported a systematic assessment of the digital skills of participants before starting the intervention. However, 14 studies reported participants’ previous experience with a digital device (Ayres & Cihak, 2010; Bereznak et al, 2012; Burckley et al., 2015; Cannella‐Malone et al, 2006; De Wit et al., 2015; Douglas, Uphold, Steffen, & Kroesch, 2018; Mechling et al., 2009; Mechling & O’Brien, 2010; Shepley, Spriggs, Samudre, & Elliot, 2018; Smith et al., 2016; Smith, Shepley, Alexander, Davis, & Ayres, 2015; Spriggs et al., 2015; Van Laarhoven, Blood, Chan, & Winiarski, 2012; Van Laarhoven, Kraus, Karpman, Nizzi, & Valentino, 2010). These experiences varied from playing online games to executing simple acts on a computer such as typing letters.…”
Section: Resultsmentioning
confidence: 99%
“…In three studies, support staff performed the intervention without the involvement of the researchers (Campillo et al., 2014; De Wit et al., 2015; Taber‐Doughty et al., 2010). In five other studies, the intervention was performed by a teacher without any involvement from the researchers (Cihak & Schrader, 2008; Douglas et al., 2018; Shepley et al., 2018; Spriggs et al., 2015; Van Laarhoven et al., 2012). Researchers collaborated closely with the teachers in three studies (Ayres & Cihak, 2010; Smith et al., 2015, 2016) and with support staff in only one study (Kerkhof et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many others find it mundane and even stressful (10). Research has proof that grocery shopping is a complex and distressing process (11) especially for individuals with a developmental disability in which it is a complex independent living skill (12). Nevertheless, a normal person also needs to acquire the skill to maintain a quality life.…”
Section: Background and Related Studiesmentioning
confidence: 99%
“…Similarly, Arnaud et al (6) also suggested three phases of grocery shopping namely preplanning, usage, and outcome that is corresponding to the three stages of Berndt's grocery shopping process. On the other hand, Douglas et al (12) specified that grocery shopping consists of three main steps that are writing a grocery list, locating items on a list in the grocery store aisles, and purchasing the grocery items. The first step in grocery shopping is planning where consumers will identify grocery items needed for the household and prepare a grocery list.…”
Section: Background and Related Studiesmentioning
confidence: 99%